Dry Eye A Practical Approach - Chan, Colin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This handbook is a concise, easy-to-read, practical guide that conveys the core knowledge necessary to diagnose, classify, grade, and manage dry eye disease effectively and efficiently. A series of succinct, informative chapters cover the following key topics: definition and classification, epidemiology, office-based screening and diagnostics, artificial tears, medical management, surgical management, and future directions. Current guidelines, published studies, and the personal experience of internationally recognized dry eye experts are distilled into practical tips that will be of value during daily clinical routine. Highlighted boxes are included to emphasize the most important points or clinical pearls, and tables and flow charts will further assist the eye care practitioner in using the book as a quick reference. The closing chapter presents case examples that build upon the instruction provided earlier in the book by illustrating the optimal approach to diverse scenarios that may be encountered in the clinic.
Introduction -- Definition and classification of dry eye -- Epidemiology of dry eye -- How to choose the right artificial tear -- Practical office based screening and diagnostics -- Medical management of dry eye -- Procedural / surgical management of dry eye -- Case studies -- Future directions and research.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology; Electronic books